A Budding “Good Practice”: Access to Quality, Non-Formal Education for Syrian Refugees in Lebanon - Diab, Jasmin Lilian (IJRDO- Journal of Educational Research, 2020)
According to a 2013 World Economic Forum report, Lebanon is ranked tenth in overall quality of education, and fifth in science and math. According to Muhammad Faour, a nonresident senior associate at the Carnegie Middle East Center in Beirut, "this assessment is a significant departure from the results of student achievement tests in every international test Lebanon and Qatar have participated in." The percentage of the population as a whole with at least some secondary education (aged 25 and above) is 54.2%. For the percentage of the female population with at least some secondary education, the figure drops to 38.8%. Amid this impressive and reputable system, Lebanon has suffered with waves of conflict, displacement, as well as asylum and refugee influxes which challenge this model and reputation of education each and every day. This paper looks into “good practice” in integrating the Syrian Refugee population into the educational system, as well as the model Lebanon has created in order to cope with almost an entire generation of illiteracy within its borders.